4u+44=6(u+5)

Simple and best practice solution for 4u+44=6(u+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4u+44=6(u+5) equation:



4u+44=6(u+5)
We move all terms to the left:
4u+44-(6(u+5))=0
We calculate terms in parentheses: -(6(u+5)), so:
6(u+5)
We multiply parentheses
6u+30
Back to the equation:
-(6u+30)
We get rid of parentheses
4u-6u-30+44=0
We add all the numbers together, and all the variables
-2u+14=0
We move all terms containing u to the left, all other terms to the right
-2u=-14
u=-14/-2
u=+7

See similar equations:

| 21u-98=49 | | 51=44+r/3 | | 0.47n=5.64 | | -5v+3(v+3)=29 | | 10x-5=-135 | | 0.27n=8.91 | | 6(u+5)=8u+48 | | 74=5v+39 | | q/7+85=97 | | 0.5(x-30)=33 | | 0.5(x-30)=47 | | 6x+5=9x-10=80 | | -4w+2(w-8)=-14 | | 1/2(x-30)=47 | | 8x+21=10x-3 | | 99=98+29/f | | 19m-47=86 | | 12x+24=20 | | 42=36+84/c | | -5/4+2/3y=-6/5 | | 3(7x+4)=7(2+x)-6 | | 3+3x=1+xx= | | 3k^2=-2k-3 | | 6+r/4=29 | | 2(x-2)-3(x-1)-(1-x)(x-3)=0 | | m/3/7-14=11 | | 126=10x-4 | | 90/p+18=3 | | 1.5n^2+18.5n-680=0 | | 8(y-2)=-3y+17 | | w/5+5.2=-7.3 | | (x-4)=-x+68 |

Equations solver categories